LANGUAGE IN CONSULTATION: THE EFFECT OF AFFECT AND VERB TENSE. Issue 6 (12th April 2017) - Newman, Daniel S.; Guiney, Meaghan C.; Barrett, Courtenay A.
Abstract : This study was an exploration of school consultation interactions between instructional consultants and consultees. Of specific interest was how consultants ( n = 18) and consultees ( n = 18) used verb tense and emotion words during the problem identification and analysis instructional consultation stage, similarities and differences in communication patterns, and whether verb tense and emotion words were related to perceptions of collaboration, consultee outcomes, or client outcomes. Data provided mixed support for study hypotheses. Among the findings, consultants' past tense verb use negatively correlated with the consultation relationship ( r = −.62, p = .01), consultees' present tense use correlated with better consultee outcomes ( r = .49, p = .05), and positive emotion word use by consultees was correlated with better consultee outcomes ( r = .54, p = .05). Implications of these and other findings are explored in the context of interpersonal communication during school consultation.